Experience of Nusinersen in children with proximal spinal muscular atrophy 5q in Moscow region - M. V. Panteleeva (Русский журнал детской неврологии, 2022)
Background. Proximal spinal muscular atrophy 5q (5q-SMA) is a severe autosomal recessive neuromuscular disorder characterized by progressive flaccid paralysis and muscular atrophy caused by degeneration of α-motor neurons in the anterior horns of the spinal cord resulted from mutations in the SMN1 gene encoding the survival motor neuron (SMN) protein. These patients have pronounced limitations of motor activity and their life expectancy is between several weeks and several decades. The development and implementation of causal therapy improved the quality of life and increased life expectancy of SMA patients. Nusinersen is one of the first drugs approved for SMA in the Russian Federation. It is an antisense oligonucleotide drug that increases the production of full-length SMN protein.Aim. To confirm the efficacy and safety of Nusinersen in children with type I–III SMA from Moscow region.Materials and methods. A total of 22 patients with type I–III SMA have been receiving Nusinersen since 2020. Treatment outcomes were evaluated using the Children’s Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) in children with type I SMA and Hammersmith Functional Motor Scale Expanded (HFMSE) in children with type II–III SMA.Results. All patients completed the stage of loading doses, including 1 patient treated for 5 years (18 injections), 3 patients treated for 3 years (12 injections), 10 patients treated for 2 years (9 injections), 4 patients treated for more than 1 year (6 injections), and 4 patients treated for less than 1 year (5 injections). Patients with type I SMA demonstrated increased scores after one year of therapy. Patients with type I–III SMA also had some improvement and higher HFMSE after loading doses followed by positive dynamics after 2 and 3 years of therapy.This article also contains cases that confirm the need of early treatment initiation immediately after the diagnosis.Conclusions. We corroborated the efficacy and safety of Nusinersen in routine clinical practice for children with different types of SMA.